Hands-on Kubernetes on Azure : run your applications securely and at scale on the most widely adopted orchestration platform /: run your applications securely and at scale on the most widely adopted orchestration platform. (2019) - Gopalakrishnan, Shivakumar; Lenz, Gunther
No abstract available